The rebellious spirit of romanticism as reflected within romantic aestheticism in Shelley’s Poetry - Ayyıldız, Nilay Erdem (Mahmut DEMİR, 2017)
The French Revolution (1789), fostering the thought of freedom and individuality, had an undeniable effect on the Romanticists. And poetry enabled most of them to express their sense of rebellion in an aesthetic manner. Among the enthusiastic supporters of the French Revolution in its early stages was the Romantic poet Percy Byssche Shelley (1792-1822). The aim of the study is to explore the rebellious nature of Romanticism which is very well reflected within Romantic aestheticism in Shelley’s “Ozymandias” (1817), “Ode to the West Wind” (1819), and “To a Skylark” (1820). For this, the study will refer primarily to Shelley’s own essay “A Defence of Poetry.”